Female Bodies as Objects of Sexuality in Patriarchal Culture: An Analysis of Alice Munro’s “Lichen” - Sulistya Ningtyas; Sulistya Ningrum (LITERA KULTURA : Journal of Literary and Cultural Studies, 2025)
This article examines the representation of female bodies as objects of male sexuality within a patriarchal framework in Alice Munro’s short story “Lichen” (1985). Using a feminist approach, this study applies Margaret Gullette’s theory of Age Ideology and Decline Narratives. The analysis explores how aging is constructed by culture and how the decline narratives of aging are repeatedly told in literature. Through the two contrasting, leading female characters, Munro portrays the objectification of female bodies: the older wife’s aging body is deemed unsatisfactory by her husband, while the young body of the second wife, encapsulated in a nude photograph, is reduced to an object for male gratification. Within the domestic sphere, the husband’s dominance over his wife reflects Canadian societal norms, which also becomes the setting of the story, where men are seen as leaders and women as submissive. The story’s title, “lichen,” a metaphor for female pubic hair, symbolizes the fleeting value placed on women’s bodies to satisfy male desires. Ultimately, Munro critiques cultural ideologies that perpetuate women’s objectification, challenging the social constructs that subordinate women to the sexual expectations of men.